Anti-money laundering regulation of crypto assets in Europe's smallest member state. Issue 4 (2nd October 2019) - Buttigieg, Christopher P.; Efthymiopoulos, Christos; Attard, Abigail; Cuyle, Samantha
Abstract : The paper critically examines the framework for the regulation of crypto assets in Malta, with a particular focus on anti-money laundering and funding of terrorism. It identifies the risks relating to crypto assets, and how these are addressed through Malta's Virtual Financial Assets Framework. To this end, the paper argues that the Maltese framework goes beyond the EU's fifth Anti-Money Laundering Directive. In this connection, the paper also argues that the Maltese framework could possibly be a model for a more extensive EU regime in this context. Finally, the paper sets forth recommendations towards action which may be taken at an EU level in order to address the money laundering and terrorism financing threats associated with crypto assets.